Enhancing Physical Fitness in Primary School Children Through Inclusive Sports Activities - Nikola Utvić; Lidija Marković; Radenko Arsenijević; Nikola Aksović; Bojan Bjelica; Stanimir Stojljković; Saša Bubanj; Gabriela Raveica; Daniel-Lucian Dobreci; Nicolae-Lucian Voinea; Vasile-Cătălin Ciocan; Mihaela Anghel; et al. (Children, 2025)
(1) Background: The aim of this study is to investigate whether the application of adaptive sports programs, initially designed for children with disabilities, can have a positive effect on physical fitness and body composition in healthy primary school children; (2) Methods: The sample comprised 80 participants, equally divided by gender (50% male, 50% female), with a mean age of 11.5 (SD = 0.03). They were divided into two groups, an experimental and a control group, with an even gender distribution. The research lasted 12 weeks, with additional classes allocated for the initial and the final measurements. The Eurofit test battery assessed physical fitness; (3) Results: ANCOVA revealed significant group differences in body composition variables within the total sample and gender distribution (p < 0.001). Significant differences were observed in handgrip strength (HGR), flamingo balance test (FBL), shuttle run 10 × 5 m (SHR) (p < 0.001), and also hand tapping (HTP) (p = 0.01). Participants in the experimental group outperformed the control group, highlighting the effectiveness of the intervention program. Specifically, boys in the experimental group showed significant improvements in HGR and SHR (p < 0.001), while girls improved significantly in HGR, FBL, and SHR (p < 0.001); (4) Conclusions: The experimental program, which incorporates sports elements for disabled individuals, led to significant improvements in the physical fitness parameters of children.